Effects of Occupational Noise Exposure on Blood Pressure and other Aspects of Health for Workers in Selected Industrial Places in Zakho City, Iraq - Yousif, Kamil M.; Ali, Faris M. (Science Journal of University of Zakho, 2017)
Industrial or Occupational noise play a vital role in the life of workers. This source of pollution disrupts and annoys the daily activities of workers. Occupational Noise pollution is increasingly being recognized as a physical factor in the environment that is injurious to many aspects of health. This study focuses on the industrial noise and its effects on workers. The aim of the study is to find out the possible relation between the occupational noise exposure and arterial blood pressure, pulse rate, and hearing thresholds for workers at several industrial areas in Zakho City, Kurdistan region of Iraq. The study group included 113 workers employed in twenty-one different factories (chosen randomly). All the individuals under study were men. Their ages were between 15 to 60 years. The noise level was between (76.5-98) decibels (dB(A)). In order to observe the harmful effects of the noise, a questionnaire was made for all the workers. The systolic blood pressure mean for the samples is increased by 6.07 mmHg, while the diastolic blood pressure mean is increased by 2.63 mmHg; the pulse rate mean is increased by 5.56 beats/minute. The hearing threshold levels also show a decrease in their values.